Cremanthodium wumengshanicum (Asteraceae, Senecioneae), a new species from Yunnan, China - Yang, Qin-Er; Wang, Long; Ren, Chen (Phytotaxa, 2015)
A new species, Cremanthodium wumengshanicum, is described and illustrated. It is most readily distinguishable in the genus by having 10−14 bracts subtending the head. Morphological differences between C. wumengshanicum and its putative closest allies and a distributional map of the new species are presented.